Insulin Resistance, Dyslipidemia and Cardiovascular Changes in a Group of Obese Children - Pires,António (2015)
Introduction: Obesity-related comorbidities are present in young obese children, providing a platform for early adult cardiovascular disorders. Objectives: To compare and correlate markers of adiposity to metabolic disturbances, vascular and cardiac morphology in a European pediatric obese cohort. Methods: We carried out an observational and transversal analysis in a cohort consisting of 121 obese children of both sexes, between the ages of 6 and 17 years. The control group consisted of 40 children with normal body mass index within the same age range. Markers of adiposity, plasma lipids and lipoproteins, homeostasis model assessment-insulin resistance, common carotid artery intima-media thickness and left ventricular diameters were analyzed. Results: There were statistically significant differences between the control and obese groups for the variables analyzed, all higher in the obese group, except for age, high-density lipoprotein cholesterol and adiponectin, higher in the control group. In the obese group, body mass index was directly correlated to left ventricular mass (r=0.542; p=0.001), the homeostasis model assessment-insulin resistance (r=0.378; p=<0.001) and mean common carotid artery intima-media thickness (r=0.378; p=<0.001). In that same group, insulin resistance was present in 38.1%, 12.5% had a combined dyslipidemic pattern, and eccentric hypertrophy was the most common left ventricular geometric pattern. Conclusions: These results suggest that these markers may be used in clinical practice to stratify cardiovascular risk, as well as to assess the impact of weight control programs.